Determinants of Female Primary School Enrolment in Rural Imo and Enugu States of Nigeria - Nnennaya, Ibiam (International Journal of Educational Management, 2022)
This study investigated the determinants of female children primary school enrolment in rural Imo and Enugu States of Nigeria. The study is a descriptive survey. The research provided information on the factors which hamper primary education of children in rural Nigeria, and which increased their enrolment and the influence of gender on enrolment. Based on the findings, recommendations were proffered on how to increase female children's participation in primary schools.